E-learning Skills’ Impact on Teachers’ Performance in Higher Technical Teachers’ Training College of the University of Buea, Cameroon - Lyonga, Ngemunang Agnes Ngale (Innovare Journal of Education, 2023)
The aim of this study was to evaluate the effect of E-learning skills on the performance of teachers in HTTTC Kumba. It was hypothesized that E-learning skills have no significant effect on teachers’ performance in HTTTC Kumba. A sample of 42 respondents was obtained by multistage sampling and administered a questionnaire to. The data were analyzed using frequencies and percentages for descriptive statistics, while the Chi-Square Test was used for testing the hypothesis. The results revealed that teachers in HTTTC Kumba are aware of E-learning and E-learning tools and are also of the opinion that the use of E-learning tools can improve performance, but they do not use E-learning platforms, nor do they believe that their students are better at E-learning platforms than in their traditional classrooms. It was recommended that education stakeholders should put all hands on deck to ensure a smooth integration of E-learning tools into the classroom.